Brachionus species distribution in relation to environmental characteristics in Cochin backwaters, Kerala, South India - Varghese, Molly; Krishnan, L (Indian Journal of Fisheries, 2013)
The interrelations between the species distribution of rotifers and environmental characteristics in Cochin backwaters were investigated by analysing rotifer as well as water samples collected simultaneously from nine different stations during the period from August 2000 to July 2002. Thirteen species of Brachionus viz., B. plicatilis, B. rotundiformis, B. angularis, B. urceolaris, B. rubens, B. forficula, B. caudatus, B. calyciflorus, B. bidentata, B. quadridentatus, B. patulus, B. falcatus and B. mirabilis were enumerated and quantified from the rotifer samples. Water samples were analysed for different parameters like water temperature, pH, dissolved oxygen, salinity, hydrogen sulphide, biochemical oxygen demand, alkalinity, phosphate, nitrite, chlorophyll a, total suspended solids and ammonia. The correlation coefficients were worked out between different species of Brachionus and the environmental characteristics with respect to each station separately as well as in the study area as a whole. In the study area, Brachionus rotundiformis dominated and contributed 85.76% among the thirteen species of Brachionus and showed significant positive correlations with nitrite, biochemical oxygen demand, chlorophyll a and total suspended solids. B. plicatilis was found to show significant positive relation with phosphate. B. plicatilis, B. angularis, B. rubens and B. patulus exhibited significant negative relation with salinity while they showed significant positive correlations with rainfall. Also, salinity showed significant negative correlation with B. urceolaris while B. falcatus exhibited significant positive relation with rainfall.